2013
DOI: 10.1007/s00520-013-2021-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia management and granulocyte colony-stimulating factor use in patients with solid tumours receiving myelotoxic chemotherapy—findings from clinical practice

Abstract: PurposeClinical practice adherence to current guidelines that recommend primary prophylaxis (PP) with granulocyte colony-stimulating factors (G-CSFs) for patients at high (≥20 %) overall risk of febrile neutropenia (FN) was evaluated.MethodsAdult patients with breast cancer, non-small cell lung cancer (NSCLC), small-cell lung cancer (SCLC), or ovarian cancer were enrolled if myelotoxic chemotherapy was planned, and they had an investigator-assessed overall FN risk ≥20 %. The primary outcome was FN incidence.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 37 publications
6
27
1
3
Order By: Relevance
“…age ≥ 65 years, advanced disease, history of previous febrile neutropenia) [1,6,7]. However, data from real-world practice settings have indicated that administration of filgrastim does not always concur with guidelines, with patients either not treated or given shortened courses [2,8,9,10,11]. Such suboptimal use of filgrastim is associated with poorer outcomes; for example, the risk of hospitalization for neutropenia or infection has been reported to decline with each additional day of G-CSF prophylaxis in patients with various types of cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…age ≥ 65 years, advanced disease, history of previous febrile neutropenia) [1,6,7]. However, data from real-world practice settings have indicated that administration of filgrastim does not always concur with guidelines, with patients either not treated or given shortened courses [2,8,9,10,11]. Such suboptimal use of filgrastim is associated with poorer outcomes; for example, the risk of hospitalization for neutropenia or infection has been reported to decline with each additional day of G-CSF prophylaxis in patients with various types of cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…The median duration of daily G-CSF use was only one day, indicating it was generally administered as short courses or intermittent doses during a cycle. This contrasts with the cytotoxic chemotherapy setting, where daily G-CSF is given typically consecutively on the first 5-6 days of the cycle [14,17]. Pegfilgrastim was used in around one-third of patients who received G-CSF, and pegfilgrastimtreated patients appeared to be more heavily pretreated and have more comorbidities than patients treated with daily G-CSF patients, while they were also younger and more received the standard dose of lenalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…Ostatnio przeprowadzono międzynarodowe badanie obserwacyjne, którego celem było zweryfikowanie zgodności zastosowania w praktyce zaleceń dotyczących pierwotnej profilaktyki GN z zastosowaniem G-CSF u chorych otrzymujących chemioterapię obarczoną wysokim (≥ 20%) ryzykiem GN [19]. Ocena dotyczyła 1347 chorych na raka piersi, niedrobnokomórkowego i drobnokomórkowego raka płuca oraz raka jajnika.…”
Section: Metaanalizy I Badania Populacyjneunclassified
“…Publikacja nie zawiera danych, które wskazywałyby na ewentualne szkody, które mogły-by wyniknąć z niestosowania tych zaleceń. Zwraca uwagę wysoki odsetek, blisko połowa programów chemioterapii, co do których nie można było ustalić stopnia ryzyka GN, co czyni stosowanie zaleceń pierwotnej profilaktyki bardzo problematycznym i pozostawia decyzję lekarza niesprecyzowanym przesłankom [19].…”
Section: Metaanalizy I Badania Populacyjneunclassified